VISUALISASI DATA OPINI PUBLIK MENGGUNAKAN LOOKER STUDIO (STUDI KASUS PEMILIHAN UMUM PRESIDEN INDONESIA 2024) - Eko Prasetyo Wicaksono; Paniran (JURNAL ILMIAH INFORMATIKA, 2024)
In 2024, Indonesia held presidential and vice presidential elections. Before the election took place, researchers gathered sentiment data from X and news sources from January 1, 2023 to September 1, 2023. The data collected was not well-visualized, resulting in suboptimal information. For this study, researchers applied data visualization using Google Looker Studio, which enables data presentation in table and graphic formats, making it more engaging. Data will be stored in BigQuery, which is connected to Looker Studio. The results of the study showed that the validity of the data based on its source was 50.1% real and 49.9% fake. There were five top topics for each candidate, including Public Figure, Leader, Political Policy, Community, and Election. Based on the sentiment flow analysis, most data originated from news sources and the rest from X social media.